Composantes multidimentionnelles de l’arbitrage : de la considération locale à l’interculturalité internationale - Wehbe, Fatima Sara (Normandie Université, 2016)
La mondialisation a permis l’instauration de plusieurs institutions d’arbitrage. Cette multitude de choix offerte aux investisseurs pourrait induire les parties à choisir une institution défavorable quant à la résolution de leur litige. L’objectif de la thèse est de présenter un modèle de gestion pour les juristes qui facilite le choix de la juridiction la plus efficace ceci avec la mise en œuvre d’un tableau de notation associant des critères multidimensionnels accordant une notation selon le degré d’importance vue par les parties. A ce sujet, le tableau mis en place regroupe les quatre juridictions les plus connues internationalement qui sont les juridictions étatiques, la CCI, le CIRDI et la CNUDCI. L’arbitrage est composé de plusieurs fondements qui lui accordent sa spécificité. L’analyse multidimensionnelle permettrait donc de faire une analyse arithmétique des valeurs comparatives des composantes juridiques et extra-juridiques de l’arbitrage qui forment le tableau de notation afin de faciliter la prise de décisions des investisseurs. Afin de vérifier l’efficacité du tableau de notation, un questionnaire a été adressé aux investisseurs ainsi que des interviews effectuées avec des juristes ont permis de déceler l’impact de l’expérience sur le choix du centre le plus efficace. L’étude de cas de l’affaire COMMISIMPEX est un exemple de l’effet du choix inefficace sur la résolution du litige et explique comment l’expérience pourrait affecter la décision de l’institution d’arbitrage le plus efficace à la résolution du litige. Pour en conclure qu’il n’y a pas de juridiction intrinsèquement meilleure que les autres. Il faut donc procéder au cas par cas et selon ce que les parties recherchent suite à leur litige, pour en déduire la juridiction ou l’institution qui leur serait la plus favorable afin de leurs garantir le plus de droits lors de la résolution de leur litige. Globalization has established several arbitral institutions. They offer a multiple of choices to the investors that could induce the parties to choose an unfavorable institution.The aim of this thesis is to present a management model for jurist which facilitates the choice of the most efficient jurisdiction in resolving their dispute, with the implementation of a scoring table combining multidimensional criteria, giving a rating according to the degree of importance for the parties. In this regard, the table regroup four of the most well-known internationally jurisdiction, the State court, the ICC, the ICSID and the UNICITRAL. Arbitration is composed of several fundaments that give it its specificity. Multidimensional analysis thus would make an arithmetical analysis of the comparative values of the legal and extra-legal components of arbitration which form the scoring table to facilitate decision making of investors. To verify the effectiveness of the scoring table a questionnaire was sent to investors as well as an interview conducted with lawyers have identifies the impact of the experience on the choice of the most efficient arbitral center. The Case study of COMMISIMPEX is an example of the effect of inefficient choice on the resolution of the dispute and how the experience may affect the decision of the most effective arbitration institution to the resolution of the dispute. To conclude none of the jurisdiction is inherently better than the others. We must proceed case by case and according to what the parties are looking after their dispute, to deduce the court or institution that would be most favorable to them by guarantying more rights in the settlement of their dispute.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Interculturality; Interculturalité; International commercial arbitration; Pluralisme juridique; Règlement de conflits

L’arbitrage institutionnel OHADA : Instrument émergent de sécurisation juridique et judiciaire des activités économiques - Diakité, Moussa (Université Toulouse 1 Capitole, 2016)
Devant le ralentissement des investissements en Afrique, il s’est avéré incontournable de reconstruire un ensemble juridique moderne adapté à l’exigence de protection des activités économiques. Les Présidents des pays, essentiellement de la zone franc, ont ainsi signé le 17 octobre 1993 le Traité relatif à l’harmonisation du droit des affaires en Afrique visant à garantir la sécurité juridique et judiciaire. Le droit issu de ce traité a donné naissance à divers Actes uniformes dont l’Acte uniforme relatif à l’arbitrage. L’objectif de notre étude a été d’analyser, principalement à partir de ce texte et sa pratique, dans quelle mesure les opérateurs économiques bénéficient, par l’arbitrage, d’une meilleure garantie d’encadrement de leurs activités. Si l’arbitrage apparait comme étant un instrument pertinent en termes de protection des investissements, c’est qu’il allie deux exigences fondamentales : la liberté ainsi que la sécurité. En effet, la liberté des parties et des arbitres est au fondement de la procédure arbitrale, garantissant aux opérateurs économiques l’assurance d’une justice plus adaptée aux exigences internationales. L’arbitrage doit également offrir une sécurité juridique dans la résolution des conflits permettant de sauvegarder les intérêts des parties tout en assurant l’efficacité de la sentence arbitrale.
Keywords: Arbitrage; Arbitrage OHADA; Arbitrage commercial international; Arbitragem; Arbitration; Investissements; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Sécurité juridique

Réflexion sur l’arbitrage dans l’espace OHADA - Diallo, Abdou (Université de Perpignan, 2016)
L’arbitrage est la motivation première de la création de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) pour lutter contre l’insécurité juridique et promouvoir son développement. Cet arbitrage s’inspire des règles matérielles de l’arbitrage international qui accorde une importance particulière à la volonté des parties.L’arbitrage dans l’espace OHADA est régi par le Traité, un acte uniforme et le règlement d’arbitrage de la Cour Commune de Justice et d’Arbitrage(C.C.J.A).Le droit de l’arbitrage a certes amélioré le cadre normatif surtout dans les pays qui n’en disposaient pas, mais au bout de plus d’une décennie d’existence, cet arbitrage est confronté à de nombreuses difficultés d’application. Ces difficultés proviennent de ces acteurs (parties, arbitres et juge national).Ainsi, notre réflexion vise à analyser les difficultés d’application à partir du contentieux arbitral et à proposer des mesures susceptibles d’améliorer le droit et la pratique de l’arbitrage.
Keywords: Afrique; Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; CCJA; Common Court of Justice and Arbitration; Cour Commune de Justice et d'Arbitrage; Exéquatur; Ohada; Organisation pour l'harmonisation en Afrique du droit des affaires

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
https://rgu-repository.worktribe.com/output/246435/arbitrability-and-public-policy-an-african-perspective
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa - Onyema, Emilia (2016)
This second conference in the SOAS Arbitration in Africa Conference series examined how African judges can better support the growth of arbitration. The conference was hosted by the The Lagos Court of Arbitration in their premises in Lagos, Nigeria from 22-24 June 2016. This conference booklet contains some of the papers and slides, and photographs from the conference.
Pages: 1-142
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Courts; Judges; Rôle; Support

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
URI: http://webcat.warwick.ac.uk/record=b3059548~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

L'intervention du juge dans la procédure arbitrale - Najib, Mohamed El Mehdi (Université de Bordeaux, 2016)
L'arbitre est un juge privé, il tranche, il juge, et il détient la balance de la justice, pourtant sesdécisions ne seront exécutoires que si le juge étatique compétent le décide. Ainsi soumise aucontrôle du juge, la sentence arbitrale s'intègre dans l'ordre juridictionnel. Elle doit doncrespecter l'ordre public et, plus généralement, les principes directeurs du procès. Certes, c’estune sentence oeuvre de justice et, au même titre que les décisions des tribunaux étatiques,bénéficie de l'autorité de la chose jugée.Les textes légaux et les règles qui gouvernent la procédure arbitrale ont une très grandeimportance tant pour les parties, que pour les arbitres. Ce sont en effet ces règles, et lapossibilité de les choisir, qui participent à la spécificité de l’arbitrage.La présente thèse identifie et analyse les diverses facettes de l'intervention du juge dans laprocédure d'arbitrage. S'il s'avère d'un précieux appui à l'arbitrage, le juge est aussi chargéd'en vérifier la régularité et d'en assurer l'efficacité.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration proceeding; Judge; Juges; Procédure arbitrale

A mediação incidental como meio de solução dos conflitos trabalhistas individuais: a questão da dispensa de trabalhadores detentores da garantia provisória no emprego - Santos, Ricardo Goretti; Leite, Carlos Henrique Bezerra (Espaço Jurídico Journal of Law, 2016)
Resumo: Este artigo versa sobre a prática da mediação incidental no processo do trabalho e sua potencial contribuição para a efetiva solução de conflitos decorrentes da dispensa de trabalhadores dotados de garantia provisória do emprego. Acusa o uso desordenado da conciliação incidental, indiscriminadamente aplicada na solução de conflitos individuais situados no âmbito de relações trabalhistas, tanto circunstanciais quanto continuadas. Busca responder ao seguinte problema de pesquisa: a prática da mediação judicial incidental na Justiça do Trabalho pode contribuir para a efetiva solução de conflitos decorrentes da dispensa do trabalhador dotado de garantia provisória do emprego? Estabelece as bases do fenômeno da difusão dos métodos alternativos de solução de conflitos, no contexto do movimento universal de acesso à justiça. Desenvolve considerações sobre particularidades da conciliação e da mediação, destacando os aspectos principais de distinção entre elas. Finalmente, avalia a aplicação dos métodos autocompositivos, considerando as particularidades das controvérsias decorrentes da dispensa de trabalhadores dotados de garantia provisória no emprego. Conclui que, por objetivar a exploração aprofundada dos interesses em jogo, o fortalecimento do diálogo e da relação entre as partes, além do empoderamento dos envolvidos, a mediação judicial incidental seria a via mais adequada para a administração de conflitos decorrentes da dispensa de trabalhadores com garantia provisória do emprego. Além isso, evidencia uma proposição legislativa sobre o tema, já submetida à apreciação da Comissão de Juristas responsável pela elaboração do Anteprojeto de Lei de Arbitragem e Mediação, do Senado Federal.
Incidental mediation as a means of solving individual labor disputes: the issue of dismissal of employees holding a provisional guarantee of employment
Keywords: Arbitrage (droit du travail); Arbitragem; Arbitration; Conciliation (droit du travail); Conciliação trabalhista; Despedida arbitrária; Garantia no emprego; Labour dispute; Mediation; Mediação trabalhista; Médiation; Resolução alternativa de conflitos

L’arbitrage en droit espagnol des sociétés, à l’aune du droit comparé - Correa Delcasso, Jean-Paul (La Lettre, 2016)
Dans la présente étude, l’auteur expose l’évolution qu’a connue la pratique de l’arbitrage en droit espagnol depuis ses débuts. Il analyse, d’un point de vue pratique, les principales solutions dégagées par la jurisprudence espagnole, en ce qui concerne l’arbitrabilité d’un grand éventail de litiges, question qui s’est traditionnellement posée en droit espagnol. Il compare la situation avec celle d’autres systèmes juridiques européens culturellement proches.

Admission de la question préjudicielle posée par le juge de l’annulation de la sentence - Posocco, Laurent (La Lettre, 2016)
Le juge de l’annulation de la sentence arbitrale internationale a la faculté de demander à la Cour de justice de l’Union européenne (CJUE) de statuer sur une question d’interprétation du Traité sur le fonctionnement de l’Union Européenne (TFUE) en vertu de son art. 267.

Bonne foi de l’avocat dans la mise en œuvre de la clause compromissoire - Posocco, Laurent (La Lettre, 2016)
Ayant fait ressortir que les parties avaient eu la volonté de se soumettre à l’arbitrage, l’exigence de bonne foi pouvait leur être opposée et que les pouvoirs du cabinet d’avocats émirati étant apparents, la croyance de la société d’avocats londonienne mandatée à l’engagement des parties était légitime, la cour d’appel en a exactement déduit que le tribunal arbitral était compétent.

La responsabilité de l’arbitre et son assurance - Raibaut, Jacques (La Lettre, 2016)
La figure de l’arbitre, comme celle du juge, paraît étrangère à la responsabilité tant domine l’image de la fonction recherchée par le justiciable : dénouer le conflit qui les oppose. Au-delà de la déception que peut susciter la décision rendue chacun admet que l’indépendance, l’impartialité et la compétence sont inhérents à cette fonction et justifient que l’arbitre bénéficie d’une immunité juridictionnelle de principe qui le met à l’abri du ressentiment d’une ou des parties.

La responsabilité des centres d'arbitrage - Elatafy, Sherif (Université Jean Moulin Lyon 3, 2016)
Les litigants sollicitent les centres d’arbitrage pour diriger l’arbitrage dans toutes ses phases afin de donner une garantie supplémentaire qui assure la validité de la sentence arbitrale. Compte tenu du rôle important que les centres d’arbitrage jouent pendant l’instance arbitrale, les litigants mécontents de la sentence arbitrale ou du jugement annulant la sentence tentent d’engager la responsabilité du centre d’arbitrage dès lors qu’il a surveillé, dirigé et participé au rendu de la sentence.De plus en plus la responsabilité des centres d’arbitrage est mise en cause devant les juridictions étatiques différentes, les fonctions et les pouvoirs exercés par les centres d’arbitrage ainsi que le régime de responsabilité leur est applicable font l’objet d’une attention critique de la part de la doctrine dans plusieurs systèmes juridiques. On s’interroge sur l’origine des rapports qui lient les centres d’arbitrage aux autres acteurs de l’arbitrage, sur les obligations et les pouvoirs conférés aux centres d’arbitrage, et sur les fonctions exercées par les centres d’arbitrage pour établir enfin un régime de responsabilité homogène et pertinent à l’égard des fonctions exercées par les centres d’arbitrage qui a une vocation à s’appliquer dans la majorité des systèmes juridiques. Parties to arbitration seek arbitral institutions to administrate their arbitration in order to have an extra guarantee that ensures the validity of the arbitral award. Given the role that arbitral institutions play during the arbitral procedure, parties unsatisfied either by the arbitral award or the annulment of the award tend to claim the liability of arbitral institution for the awards it had supervised, administered and participated in.The more the allegations of liability raise against the arbitral institutions before courts, the more the issue of arbitral institutions’ functions, powers and liability becomes controversial in different jurisdictions. Therefore, the present study tends to clarify the origin of the relationship existing between arbitral institutions and other parties involved in the arbitration at issue, the duties and powers assigned to the arbitral institutions and the functions performed by the arbitral intuitions, which helps eventually in establishing a kind of liability that complies with the functions performed by the arbitral institutions and can be applied in many jurisdictions.
Keywords: Acte juridictionnel; Administrative functions; Agreement to administrate an arbitration; Approbation; Arbitrage; Arbitrage commercial international; Arbitrage institutionnel; Arbitragem; Arbitral Awards; Arbitral institutions; Arbitration; Business contract; Centre d'arbitrage; Challenging arbitrator; Civil liability; Clause exclusive de responsabilité; Condition excluding liability; Consensual protection; Contrat de direction d’arbitrage; Contrat d’entreprise; Décision institutionnelle; Examen prima facie; Faute intentionnelle; Faute lourde; Fonctions administratives; Fonctions juridictionnelles; Forum; Gross negligence; Immunity; Immunité; Institutional arbitration; Institutional decision; Judicial conduct; Judicial functions; Prima facie examination; Protection conventionnelle; Responsabilité civile; Récusation d’arbitre; Sentence arbitrale; Willful misconduct

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

La sentence arbitrale et le juge étatique : approche comparative des systèmes français et iranien - Danay Elmi, Manijeh (Université Paris 1, 2016)
En France et en Iran, le droit de l’arbitrage est le fruit d’une longue maturation historique. L’arbitrage en Iran plonge ses racines dans l’Antiquité. En raison de la culture du règlement pacifique des différends qui dominait alors, l’arbitrage s’est imposé comme le mode privilégié des règlements des différends. Dans le domaine de l’arbitrage commercial international, l’Iran s’est inspiré de la loi-type de la CNUDCI de 1997. Ce pays a également adhéré en 2001 à la Convention de New York. Le point de convergence entre les deux ordres juridiques français et iranien : ils ont cherché à instaurer des règles plus favorables pour la reconnaissance et l’exécution des sentences arbitrales, chacun ayant adopté une démarche différente. La première partie de cette étude est consacrée à la réception de la sentence arbitrale dans les deux systèmes. Seule la sentence définitive peut faire l’objet du contrôle et de l’exécution. Plus concrètement, la qualification en sentence internationale ou étrangère déterminera les règles applicables à la reconnaissance et l’exécution de celle-ci. La sentence arbitrale identifiée et reconnue est susceptible d'être contrôlée par le juge qui déterminera le sort de la sentence. La deuxième partie de notre analyse décrit ce contrôle qui peut être direct à l’occasion du recours en annulation ou indirect lors de la demande de reconnaissance et d’exécution. Ce mécanisme conduit in fine à protéger les droits de la partie gagnante et à empêcher l’abus, par la partie condamnée, des voies de recours. In France and Iran, the law of arbitration is the result of a long historical development. Arbitration in Iran finds its roots in the Antiquity. Because of a culture favoring the pacific settlement of disputes, which was prevailing at that period, arbitration imposed itself as the privileged mode in resolving disputes. In the field of international commercial arbitration, Iranian legal system has been inspired by the UNCITRAL Model Law in the promulgation of its LICA in 1997. This country has also adhered to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards in 2001. The converging point between the Iranian and French legal systems is the following: they have tried to establish the rules favoring the recognition and enforcement of arbitral awards, any of them adopting a different approach. The First Part of this study is allocated to the reception of the arbitral award in the two legal systems. Solely the final award could be subject to control and enforcement. More concretely, the qualification of the arbitral award as international or foreign award will determine the applicable rules in the matters of recognition and enforcement. The arbitral award, identified and recognized, could possibly be controlled by the judge who will determine its fate. The Second Part of our analysis describes the said control that could be direct, on the occasion of the action for setting aside the award, or indirect, when requesting the recognition and enforcement of the award. This mechanism will lead in fine to protecting the winning party’s rights and avoiding any abuse of the means of recourse by the losing party.
Issue: 2016PA01D014
Keywords: Arbitrage; Arbitrage (droit); Arbitrage commercial international; Arbitration; Arbitre; Droit comparé; Droit international; France; International commercial arbitration; Iran; Iranian legal system; Ordre public droit iranien; Reconnaissance et éxécution de sentence; Sentence arbitrale

Contrariétés entre jugements étatiques et sentences arbitrales dans l'espace OHADA - Castellane, Béatrice (Penant : revue trimestrielle de droit africain, 2016)

La cláusula med-arb en la actualidad: mediación y arbitraje vinculados - Cuéllar Tijerina, Ervey Sergio (Universitat Pompeu Fabra, 2016)
La intención de esta investigación, es realizar un breve análisis de las ventajas y desventajas que representa, la inclusión en los contratos comerciales, de una cláusula contractual que prevea la resolución de los posibles conflictos que pudiera suscitarse entre las partes, con la interpretación o el cumplimiento del contrato, a través de un ADR, que vincule en un solo proceso a la mediación y al arbitraje (Cláusula Med-Arb). Lo anterior, se pretende verificar a la luz de las disposiciones emitidas por los principales organismos en el comercio internacional, y su perspectiva de aplicación en el Derecho Español.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Derecho civil; MARD; Mediación; Mediation; Mediação; Médiation

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
https://dspace.stir.ac.uk/bitstream/1893/23090/1/Enforceability%20of%20Arbitral%20Awards%20Containing%20Interest.pdf
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

L'arbitrage commercial international par rapport à la juridiction étatique en matière de mesures provisoires et conservatoires : étude analytique et comparative - Emara, Fehr Abdelazim (Université Laval, 2016)
Depuis le milieu du XXe siècle, l'arbitrage commercial international a connu un développement phénoménal et acquis une importance significative dans le monde des transactions commerciales internationales. Il est effectivement devenu la juridiction mondiale la plus acceptable, la plus fiable et la plus usuelle pour résoudre les différends relatifs au commerce et aux investissements internationaux. Toutefois, il a rencontré des difficultés en ce qui concerne les mesures provisoires et conservatoires ce qui explique la tendance des parties à éviter d’y avoir recours devant les arbitres, au profit des juridictions étatiques pour obtenir les mesures d’urgence dont ils avaient immédiatement besoin. L’inexistence d’un régime procédural capable de bien régir cette matière était la raison principale qui a réduit l’efficacité de l’arbitrage. Pourtant, ce fait a changé grâce aux modifications majeures qui ont été apportées à la Loi type de la CNUDCI en 2006. Cette loi a établi un régime arbitral spécifique aux mesures provisoires et conservatoires. À un stade ultérieur, les règlements modifiés récemment par les centres d’arbitrage qui agissent sur la scène internationale ont beaucoup développé ce régime en le mettant en pratique. Maintenant, en présence d’un régime arbitral particulier régissant les mesures provisoires et conservatoires, il est opportun d’en évaluer en profondeur l’efficacité par rapport à celle du régime étatique classique régissant la même matière. Voilà l’objectif de cette thèse de doctorat qui présente nombre des propositions doctrinales et normatives dans le but d’améliorer autant que possible ce régime arbitral récent.
Keywords: Acte conservatoire; Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Cours d'État; Droit comparé; Mesures provisoires

La prérogative de l'arbitre de relever un moyen d'office - Gaucher, Natalia (Aix-Marseille Université, 2016)

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Milletlerarası ticari tahkime ilişkin UNCITRAL model kanununda yargılama yetkisi kavramı ve tahkim mahkemesinin yargılama yetkisinin sınırları - Ki̇tapçi, Hakan (Selçuk Üniversitesi, 2016)
447977
Keywords: Arbitration; Authority; International Arbitiation Law; Judgement; Milletlerarası Tahkim Kanunu; Tahkim; UNCITRAL Model Kanunu; UNCITRAL Model Law; Yargılama; Yetki

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
https://research-repository.uwa.edu.au/en/publications/developing-efficient-dispute-resolution-solutions-for-internation The UWA Profiles and Research Repository
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

دور المحكم في الخصومة التحكيمية - حمودي, سمية (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة أهم عنصر من عناصر عملية التحكيم، ألا وهو دور المحكم في خصومة التحكيم، وذلك من خلال معرفة شروط وإجراءات اختاره ومركزه القانوني وسلطاته والتزاماته . و قد بدأت الدراسة بمقدمة تضمنت العناصر الرئيسية للبحث وتناولنا ف الفصل الأول التعريف بالمحكم من خلال بيان معناه وتميزه عن القاضي والخبير والمصالح والوكيل، كذلك بيان الشروط الواجب توافرها في المحكم، كما تم توضيح المركز القانوني للمحكم في خصومة التحكم وكذا بيان طرق تشكيل هيئة التحكيم. كما تناولنا سلطات المحكم، سواء كانت ناشئة عن اتفاق التحكيم، أم المخولة له بموجب القانون، وبيان الالتزامات المرمية على عاتقه أثناء مباشرته لمهمته، وكل ذلك من خلال الفصل الثاني. ومن أهم النتائج التي خلصت إليها الدراسة، هي أن المحكم يتمتع بسلطات واسعة في خصومة التحكيم، إلا أن هذه السلطات الواسعة ليست مطلقة بلا قيود، وإنما يفرض على المحكم عدة التزامات منذ قبوله مهمة التحكيم وحتى صدور الحكم الفاصل في النزاع مرورا بالتزاماته أثناء سير الاجراءات مع مراعاة احترام المبادئ الأساسية للتقاضي. Cette étude portait sur l'élément le plus important du processus d'arbitrage, à savoir le rôle d'arbitre dans l'arbitrage des différends, et grâce à la connaissance des conditions et des procédures choisies statut juridique, pouvoirs et obligations. L'étude a commencé par une introduction comprenait les principaux éléments de la recherche et nous traitée dans le premier arbitre de définition de chapitre à travers les moyens de déclaration et de le distinguer du juge et expert, des intérêts et de l'agent, ainsi que la déclaration des conditions à remplir par l'arbitre, a également clarifier le statut juridique d'un arbitre dans le contrôle des différends, ainsi qu'une description des moyens de la formation du tribunal. Comme nous approchions les autorités de l'arbitre, que ce soit en raison de la convention d'arbitrage, ou qui lui sont conférés en vertu de la loi, et la déclaration des obligations jetées sur lui-même pendant l'exécution de leur mission, et tout au long du deuxième trimestre. Parmi les résultats les plus importants de l'étude, il est que l'arbitre dispose de larges pouvoirs à l'arbitrage des différends, mais ces larges pouvoirs est pas absolue, sans restrictions, mais a imposé à l'arbitre plusieurs engagements depuis accepter la tâche d'arbitrage et jusqu'à la délivrance de l'arbitre décisif dans le conflit par ses obligations au cours de la procédure, avec en tenant compte du respect des principes de base du litige
Keywords: Arbitrage des différends; Arbitration; Arbitre; Obligations de l'arbitre; Pouvoirs de l'arbitre; Statut juridique; Tribunal arbitral; التزامات المحكم; الخصومة التحكيمية; المحكم; المركز القانوني; سلطات و; هيئة التحكيم